ANALISIS PENGARUH KUALITAS LAYANAN TERHADAP MINAT BELI ULANG (STUDI EMPIRIS PADA PT. SRIWIJAYA AIR DISTRIK SEMARANG ) - Hadani, Aditya Lazuardi (JURNAL BISNIS STRATEGI, 2008)
This Research has aim to analyze factors that induce Pre Flight Service. In Flight Service and Post Flight Service are going to influence the Repurchase Intension.The main question in this research is how to increase sales. Based on this question, a theoretical model and 4 hypothesis are proposed to be assessed using SPSS. Samples of this research are 100 consumers of PT. Sriwijaya Airlines Distic SemarangThese results show that is possible to be increased through increasing Pre Flight Service, In Flight Service and Post Flight Service which can be increased Service Quality; and which that is possible to be increased through increasingService Quality, can be increased Repurchase Intension